2022
DOI: 10.1021/acscatal.2c03338
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Air-Stable and Reconstruction-Inhibited Transition Metal Sulfide Catalysts via Tailoring Electron-Deficient Distribution for Water Oxidation

Abstract: In promising transition metal sulfide catalysts, the extraordinary instability under air exposure and oxygen evolution reaction (OER) catalysis severely degrades their activity and stability in the electrochemical water splitting reaction, inhibiting their practical applications. Herein, guided by a theoretical mechanism study, it is disclosed that the adsorbing ability and electronic interaction for molecular oxygen will be significantly weakened in nickel disulfide (NiS 2 ) by constructing an electron-defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…[ 80 ] Cheng and co‐workers reported that the adsorbing ability and electronic interaction for molecular oxygen could be significantly weakened in NiS 2 by constructing an electron‐deficient distribution on NiS sites with N atom introduction, which efficiently inhibits the process of O 2 adsorption and electrophilic activation during oxidation, thus achieving air‐stable capacity for NiS 2 . [ 81 ] In addition, others have created vacancy defects in catalyst itself to accelerate reaction kinetics. Our group recently studied how oxygen vacancy (Vo) dynamically changes and affects the OER in Co 3 O 4 catalyst.…”
Section: Impact Of Dynamic Evolution Of Defects To Electrocatalysismentioning
confidence: 99%
“…[ 80 ] Cheng and co‐workers reported that the adsorbing ability and electronic interaction for molecular oxygen could be significantly weakened in NiS 2 by constructing an electron‐deficient distribution on NiS sites with N atom introduction, which efficiently inhibits the process of O 2 adsorption and electrophilic activation during oxidation, thus achieving air‐stable capacity for NiS 2 . [ 81 ] In addition, others have created vacancy defects in catalyst itself to accelerate reaction kinetics. Our group recently studied how oxygen vacancy (Vo) dynamically changes and affects the OER in Co 3 O 4 catalyst.…”
Section: Impact Of Dynamic Evolution Of Defects To Electrocatalysismentioning
confidence: 99%
“…Numerous studies of transition metal-based materials including oxides, [23][24][25][26] sulfides [27][28][29] and phosphides [30][31][32][33][34] have been proven to show outstanding ability for dissociating H-OH bonds in alkaline media. 35,36 Typically, by coupling the metal Pt with transition metal oxides (TMOs), 37 the alkaline HER (A-HER) activity of the catalyst can be significantly boosted due to the synergetic catalytic effect of oxide sites with highly efficient water adsorbing and dissociating ability.…”
Section: Introductionmentioning
confidence: 99%
“…13–16 For commercial Pt catalysts, the electrocatalytic performance under alkaline conditions is observed to be significantly lower than that under acidic conditions, resulting from the weak interaction of Pt and H 2 O 17 and sluggish Volmer-step (H 2 O + e − → H* + OH − ), 18,19 caused by the high free energy of water dissociation on the full-filled 5d orbitals of Pt under an alkaline medium. 20–22 Numerous studies of transition metal-based materials including oxides, 23–26 sulfides 27–29 and phosphides 30–34 have been proven to show outstanding ability for dissociating H–OH bonds in alkaline media. 35,36 Typically, by coupling the metal Pt with transition metal oxides (TMOs), 37 the alkaline HER (A-HER) activity of the catalyst can be significantly boosted due to the synergetic catalytic effect of oxide sites with highly efficient water adsorbing and dissociating ability.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a suitable tensile strain may significantly improve the OER performance of NiTe/Ni 2 P. However, excessive strain would lead to failure due to the lattice collapsing into another crystal phase, which coincides well with experimental results, where the NiTe/Ni 2 P with excessive strain shows apparent cracks (Figures S10, S11, and S41) when the amount of NaH 2 PO 2 reaches 2.0 g. Interestingly, the OH* adsorption free energy of Ni 2 P (201) exceeds 0 eV in the ∼5−6% tensile strain range, so the oxygen species can reversibly adsorb and desorb on the Ni 2 P (201) surface, which inhibits the irreversible phase transition of Ni 2 P into NiOOH. 63,64 Additionally, the metal salt protection layer is produced at a low voltage, therefore significantly boosting the structural stability of NiTe/Ni 2 P. On the contrary, when Ni 2 P either does not have a lattice strain or has a compressive strain, the strong adsorption of the oxygen species enhances the irreversible conversion of Ni 2 P to NiOOH. 60,61,65,66 In short, the above analysis indicates that the lattice strain between NiTe and Ni 2 P in NiTe/Ni 2 P not only can boost the OER activity of the sample by optimizing the electronic structure but also can efficiently improve the stability of catalysts by inhibiting the structurally irreversible transition caused by the continuous oxidation of the catalyst.…”
Section: ■ Introductionmentioning
confidence: 99%